2013
DOI: 10.1007/s00296-013-2864-3
|View full text |Cite
|
Sign up to set email alerts
|

Variants in TNFSF4, TNFAIP3, TNIP1, BLK, SLC15A4 and UBE2L3 interact to confer risk of systemic lupus erythematosus in Chinese population

Abstract: Our previous genome-wide association studies on SLE have identified several susceptibility genes involved in NF-κB signaling pathway, including TNFSF4, TNFAIP3, TNIP1, BLK, SLC15A4 and UBE2L3. The aim of this study is to investigate the association model (additive, dominant, recessive) of these genes and search for possible gene-gene interactions between them. In this study, we explored the association model of these six genes and search for possible gene-gene interactions based on identified single-nucleotide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 41 publications
1
23
0
1
Order By: Relevance
“…Over the past decade, genome‐wide association studies (GWAS) identified numerous NF‐κB susceptibility loci associated with autoimmune disease. Among these loci, TNIP1 polymorphisms have been strongly associated with psoriasis, psoriatic arthritis, SLE, and systemic sclerosis (SSc) (Figure ). Nair et al identified rs17728338 as a risk variant for psoriasis in patients of European ancestry .…”
Section: Tnip1 As a Disease Susceptibility Genementioning
confidence: 99%
See 1 more Smart Citation
“…Over the past decade, genome‐wide association studies (GWAS) identified numerous NF‐κB susceptibility loci associated with autoimmune disease. Among these loci, TNIP1 polymorphisms have been strongly associated with psoriasis, psoriatic arthritis, SLE, and systemic sclerosis (SSc) (Figure ). Nair et al identified rs17728338 as a risk variant for psoriasis in patients of European ancestry .…”
Section: Tnip1 As a Disease Susceptibility Genementioning
confidence: 99%
“…Han et al reported association of another TNIP1 variant, rs10036748, with SLE in the Chinese Han population . In replication studies, rs10036748 was verified as a risk variant for SLE in the Chinese Han population . Although these studies provided evidence for association between TNIP1 polymorphisms and SLE, they were limited in terms of ethnic diversity.…”
Section: Tnip1 As a Disease Susceptibility Genementioning
confidence: 99%
“…Several single nucleotide polymorphisms (SNPs) in TNFSF4 gene have been identified to be associated with SLE. In our study, we investigated four SNPs in the TNFSF4 gene: rs2205960, rs1234315, rs8446748 and rs704840, which have been reported to be significantly associated with SLE in the Asian populations (Chang et al, 2009;Han et al, 2009;Yang et al, 2010;Zhou et al, 2012;Zuo et al, 2014). We aimed to further examine the allelic and genotypic frequencies and association of each of these SNPs with SLE in the three main ethnic groups (Malays, Chinese and Indians) in Malaysia as well as in the Malaysian population as a whole by grouping the results.…”
Section: Introductionmentioning
confidence: 99%
“…This is the first identified with rheumatoid arthritis . Over the last decade, numerous studies have investigated the relationship between TNFAIP3 gene polymorphisms association with SLE .…”
Section: Introductionmentioning
confidence: 99%